The optimal laser fiber core size for endourological performance: a systematic review - Ibrahim, Muhidin Hassan; Tozsin, Atinc; Rassweiler-Seyfried, Marie-Claire; Soyturk, Selim; Gadzhiev, Nariman; Kallidonis, Panagiotis; Knoll, Thomas; Guven, Selcuk; Ahmed, Kamran (Minimally invasive therapy & allied technologies, 2025)
This review assesses how fiber core size impacts energy delivery, degradation, safety, durability, fracture resistance, retropulsion, and flexibility. A comprehensive search of PubMed and Cochrane databases identified 1,148 articles comparing fiber core sizes. After removing 109 duplicates and excluding 996 articles based on titles and abstracts, 43 full-text articles were reviewed. Of these, 30 were excluded for lacking relevant parameters or being review articles. One article was added manually, resulting in 14 studies in the final analysis. Smaller core fibers (≤300 μm) provide higher energy delivery and greater flexibility, making them ideal for lithotripsy. However, they are more prone to tip degradation and have lower durability under high-power conditions. Larger fibers (≥300 μm) demonstrate better energy efficiency, reduced degradation, and higher fracture resistance, making them suitable for high-energy applications like prostate enucleation. Thermal safety is influenced by both fiber size and irrigation; smaller fibers maintain safer temperatures with adequate irrigation. Retropulsion is less in small and large fibers compared to medium-core fibers (365-550 μm). Smaller fibers (150 μm) generate larger bubbles than larger fibers (272 μm). Laser fiber core size influences energy delivery, durability, thermal safety, and flexibility, affecting endourological outcomes. Appropriate fiber selection improves procedural efficiency and safety.